Altitude dependence of nightside Martian suprathermal electron depletions as revealed by MAVEN observations. Issue 21 (5th November 2015) - Steckiewicz, M.; Mazelle, C.; Garnier, P.; André, N.; Penou, E.; Beth, A.; Sauvaud, J.‐A.; Toublanc, D.; Mitchell, D. L.; McFadden, J. P.; Luhmann, J. G.; Lillis, R. J.; et al.
Abstract: The MAVEN (Mars Atmosphere and Volatile EvolutioN) spacecraft is providing new detailed observations of the Martian ionosphere thanks to its unique orbital coverage and instrument suite. During most periapsis passages on the nightside ionosphere suprathermal electron depletions were detected. A simple criterion was implemented to identify the 1742 depletions observed from 16 November 2014 to 28 February 2015. A statistical analysis reveals that the main ion and electron populations within the depletions are surprisingly constant in time and altitude. Absorption by CO2 is the main loss process for suprathermal electrons, and electrons that strongly peaked around 6 eV are resulting from this interaction. The observation of depletions appears however highly dependent on altitude. Depletions are mainly located above strong crustal magnetic sources above 170 km, whereas the depletions observed for the first time below 170 km are globally scattered onto the Martian surface with no particular dependence on crustal fields. Key Points: MAVEN observes on almost each periapsis in the nightside ionosphere suprathermal electron depletions Observed depletions are populated by 6 eV electrons resulting from absorption by CO2 and by 3 eV O2 + The geographical distribution of nightside suprathermal electron depletions depends on altitude